Comparison of postoperative pain after instrumentation with TruNatomy or ProTaper Next Ni-Ti systems in mandibular molars with asymptomatic apical periodontitis: a randomized clinical trial - Çağla Vardar Korkman; Faruk Haznedaroğlu (BMC Oral Health)
Abstract Background Ni-Ti instruments with varying design features may lead to different levels of postoperative pain, which is a significant clinical concern, particularly in previously asymptomatic teeth. Therefore, the purpose of this randomized clinical trial is to compare postoperative pain following instrumentation with TruNatomy versus ProTaper Next Ni-Ti systems in mandibular molars with asymptomatic apical periodontitis. Methods 90 healthy participants were randomly assigned to two groups: TruNatomy (TN) or ProTaper Next (PTN) instruments. After single-visit root canal treatments, participants were asked to rate their postoperative pain levels at 6, 12, 24, 48, and 72 h and seven days later, using the Numerical Rating Scale (NRS) through an online questionnaire. In cases of pain, 400 mg of ibuprofen was prescribed. Data from 80 participants were finally included in the analysis. Data were analyzed using the Mann-Whitney U, Friedman, and Fisher’s Chi-Square tests (p < 0.05). Results There was no statistically significant difference in postoperative pain intensity at 6, 12, 24, and 48 h and seven days between the groups (p > 0.05). At the 72-hour time point, TN group showed statistically higher postoperative pain intensity (p < 0.05). No statistically significant differences in the incidence of postoperative pain were observed at any of the time points (p > 0.05). Analgesic intake and flare-up incidence were not significantly different between the groups (p > 0.05). Conclusion Postoperative pain levels were not significantly influenced by the type of rotary Ni-Ti instrument. Both TN and PTN instruments led to low-level and similar postoperative pain intensity, minimal analgesic use, and a low incidence of flare-ups in teeth with asymptomatic apical periodontitis. Trial registration ClinicalTrials.gov ID NCT06545773, Registration Date 8 August 2024 (retrospectively registered).